Agricultural research, biometry and statistics - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Biometry is nor just the mechanical application of mathematical procedures, but is a coherent concept which must beunderstood before implementing or analysing scientific experiments. In recent years the quality of scientific papers published...